2021
DOI: 10.1155/2021/5171618
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Brain Functional Connectivity Strength and Effective Connectivity in Patients with Type 2 Diabetes Mellitus

Abstract: Alterations of brain functional connectivity in patients with type 2 diabetes mellitus (T2DM) have been reported by resting-state functional magnetic resonance imaging studies, but the underlying precise neuropathological mechanism remains unclear. This study is aimed at investigating the implicit alterations of functional connections in T2DM by integrating functional connectivity strength (FCS) and Granger causality analysis (GCA) and further exploring their associations with clinical characteristics. Sixty T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This prefrontal hub not only showed decreased srFCD with increasing insulin resistance in the pre-diabetic group, but also showed decreased FC with the left posterior cingulate cortex and increased FC with the right parahipocampal gyrus in prediabetic individuals. While these FC anomalies with regions of the default mode network were not associated with changes in cognitive function, they are reminiscent of the altered rs-FC patterns observed in middle-aged and older adults with diabetes, which were indeed accompanied by lower scores on different cognitive tests (Hoogenboom et al, 2014;Cui et al, 2015;Guo et al, 2021). The lack of relationship with cognition may be due to the fact that glucose dysregulation and insulin resistance were not sufficiently severe, or that our neuropsychological battery did not include tests sensitive enough to detect such impairment.…”
Section: Discussionmentioning
confidence: 84%
“…This prefrontal hub not only showed decreased srFCD with increasing insulin resistance in the pre-diabetic group, but also showed decreased FC with the left posterior cingulate cortex and increased FC with the right parahipocampal gyrus in prediabetic individuals. While these FC anomalies with regions of the default mode network were not associated with changes in cognitive function, they are reminiscent of the altered rs-FC patterns observed in middle-aged and older adults with diabetes, which were indeed accompanied by lower scores on different cognitive tests (Hoogenboom et al, 2014;Cui et al, 2015;Guo et al, 2021). The lack of relationship with cognition may be due to the fact that glucose dysregulation and insulin resistance were not sufficiently severe, or that our neuropsychological battery did not include tests sensitive enough to detect such impairment.…”
Section: Discussionmentioning
confidence: 84%
“…For example, some studies have reported that reduced FC is associated with an increase in FBG ( Xia et al, 2013 ; Chen et al, 2014 ; Liu et al, 2016 ). In contrast, one study reported that fasting plasma glucose was positively correlated with the FC between the left fusiform gyrus and the right MFG ( Guo et al, 2021 ). In line with this previous study, our present study also found a positive correlation between FBG and the FC between the right caudate nucleus and LIFG, LFP, RFP, and RMFG in patients with T2DM.…”
Section: Discussionmentioning
confidence: 95%
“…The fusiform gyrus (FFG) is crucial for advanced-level object recognition and is associated with various neural pathways involved in processing visual food cues. The middle frontal gyrus (MFG) is a part of the dorsolateral prefrontal cortex and plays a key role in dietary control, food craving, and metabolic regulation ( 18 , 46 ). The PCU is also a core node of the DMN, exhibiting a remarkably high metabolic rate and serving as a linchpin in facilitating the synthesis of external information and internal representations (like episodic memories, self-relevant information, and subjective value processed by other DMN regions) ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the studies discussed above only examined the static functional connectivity within the DMN, and only a few concentrated on dynamic and effective functional connectivity, which can track changes in the strength of the connections between various regions of interest over time and capture spontaneously recurring patterns of functional connectivity ( 16 ). According to the available results of casual analysis, patients with T2DM showed altered DEC between the left fusiform gyrus and bilateral lingual gyrus and right medial frontal gyrus (MFG), the right SFG and bilateral frontal regions, as well as between left hippocampus (LHIP) and right hippocampus (RHIP), occipital cortex and cerebellum ( 17 , 18 ). Effective connectivity network is a graph model consisting of nodes and directed edges, where the nodes represent brain regions and the directed edges portray the causal effect of neural activity exerted by one brain region on another brain region, and the edge-related connection parameter indicates the connection strength of the edge ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%